2020
DOI: 10.1105/tpc.20.00248
|View full text |Cite
|
Sign up to set email alerts
|

A CEP Peptide Receptor-Like Kinase Regulates Auxin Biosynthesis and Ethylene Signaling to Coordinate Root Growth and Symbiotic Nodulation in Medicago truncatula

Abstract: Because of the large amount of energy consumed during symbiotic nitrogen fixation, legumes must balance growth and symbiotic nodulation. Both lateral roots and nodules form on the root system, and the developmental coordination of these organs under conditions of reduced nitrogen (N) availability remains elusive. We show that the Medicago truncatula COMPACT ROOT ARCHITECTURE2 (MtCRA2) receptor-like kinase is essential to promote the initiation of early symbiotic nodulation and to inhibit root growth in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 70 publications
1
34
0
Order By: Relevance
“…Currently, peptides, miRNAs, and hormones are all known to mediate nitrogen demand signaling under low nitrate conditions by binding to the receptors or by affecting gene expression in root and or shoot [ 59 , 61 , 62 ] (see Figure 2 b). A root generated peptide from the C-TERMINALLY ENCODED PEPTIDE (CEP) family, MtCEP1, is the only well-studied peptide signal of M. truncatula nitrogen demand signaling, exhibit negative effects on lateral root formation and positive effect on nodulation under low N conditions [ 61 ] ( Figure 2 b).…”
Section: Signaling To Inhibit Nodule Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, peptides, miRNAs, and hormones are all known to mediate nitrogen demand signaling under low nitrate conditions by binding to the receptors or by affecting gene expression in root and or shoot [ 59 , 61 , 62 ] (see Figure 2 b). A root generated peptide from the C-TERMINALLY ENCODED PEPTIDE (CEP) family, MtCEP1, is the only well-studied peptide signal of M. truncatula nitrogen demand signaling, exhibit negative effects on lateral root formation and positive effect on nodulation under low N conditions [ 61 ] ( Figure 2 b).…”
Section: Signaling To Inhibit Nodule Formationmentioning
confidence: 99%
“…The CEP1-CRA2 dependent enhanced expression of miR2111 in shoots (see AON section below) was shown to target the mRNAs of the genes TOO MUCH LOVE 1 ( TML1 ) and TML2 in roots, lowering the transcript levels of both genes presumably to maintain susceptibility to symbiotic nodulation [ 59 ] ( Figure 2 b). A separate study showed that CEP1-activated MtCRA2 phosphorylates MtEIN2 (ETHYLENE INSENSITIVE 2), preventing its cleavage and repressing an ethylene response, thus promoting the root susceptibility to rhizobia [ 62 ] ( Figure 2 b). Exogenous ethylene treatment during the first 24 to 48 h of rhizobial inoculation is enough to suppress nodulation in wild type plants [ 65 ].…”
Section: Signaling To Inhibit Nodule Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…C-terminally encoded peptides (CEPs) are small, secreted peptides containing 15 highly conserved amino acids in the mature state, which participate in root development and other multiple physiological activities, such as symbiotic nitrogen fixation and nitrate uptake ( Ohyama et al , 2008 ; Imin et al , 2013 ; Tabata et al , 2014 ). These peptides are derived from non-functional pre-propeptides, processed by proteolytic cleavage and the addition of post-translational modifications (PTMs), and then transferred to the apoplast, stem xylem, or possibly the endoplasmic reticulum (ER), where they function as ligands with their corresponding receptors to trigger downstream responses ( Okamoto et al , 2016 ; Patel et al , 2018 ; Zhu et al , 2020 ). Genes from the CEP family are present across seed plants and have evolved via duplication and variation, which has led to the diversification of CEP -associated regulatory networks ( Delay et al , 2013a ; Ogilvie et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Medicago , MtCEP1 is expressed in primary root tips, vascular tissue, and lateral organ primordia, particularly under nitrogen (N) limitations (Imin et al, 2013). The Medicago COMPACT ROOT ARCHITECTURE2 (MtCRA2) receptor-like kinase is essential for inhibiting root growth in response to low N, leading to a repression of MtYUC2 auxin biosynthesis gene expression (Zhu et al, 2020). Together, these data suggest a relationship between CEP peptide signaling and auxin.…”
Section: Introductionmentioning
confidence: 99%